The effects of bail-ins on bail-out expectations in the European Banking sector - Edelmann, Bernd Michael Kay (2017)
In the aftermath of the Great Recession, sovereign guarantees and the associated bail-out ex-pectations caused a distortion in the cost of funding and risk-taking behaviour of financial in-stitutions. The Bank Recovery and Resolution Directive (BRRD) aims to achieve financial sta-bility through transparency and incentivizing market discipline. The central tool of the BRRD, the bail in, is a burden-sharing mechanism reallocating the cost of the gone concern of financial institutions. Forcing shareholders and creditors to participate in potential losses must increase monitoring, thus reducing the moral hazard of large financial institutions. If the directive is credible, these changes in bail-out expectations must be reflected in the security prices of all affected banks. As changes in regulation are introduced over several years, effects on market prices are difficult to observe. I show that the recurring resolution events between 2011 and 2016 across several Eurozone countries affected bail-out expectations, reaching a critical level in 2013. The write down of junior debt in Cyprus caused highly significant reactions on bank charter values and CDS spreads. From 2014 to 2016, effects were inconsistent and lacked di-rection. This decrease in market reactions points to the achievement of bail-in expectations through commitment and consistent implementation. Bail-in expectations imply the anticipa-tion of a bail-in in case of bank financial distress, which requires strict and diligent monitoring.